Etnography of The Communication Memayu Buyut Trusmi Ritual in Cultural Preservation - Salma Syifa Zofia; Siti Khumayah; Abdul Jalil Hermawan (Salus Publica: Journal of Community Service, 2026)
The Memayu Buyut Trusmi ritual is a traditional custom that is still preserved by the Trusmi community as part of their efforts to preserve local culture. This study aims to analyze the role of communication practices in the Memayu Buyut Trusmi ritual in maintaining cultural values, collective identity, and social solidarity within the community. This study uses a qualitative approach with a communication ethnography method. Data were obtained through participatory observation and in-depth interviews with religious leaders, key figures, and the community directly involved in the ritual. Data analysis was conducted using Dell Hymes' SPEAKING framework, which includes the elements of Setting, Participants, Ends, Act Sequence, Key, Instrumentalities, Norms, and Genre. The results of the study show that the Trusmi Memayu Buyut Ritual is a structured and meaningful cultural communication event. Cultural preservation is not only reflected in the physical maintenance of sacred buildings through the replacement of welit, but also through ritual communication that is symbolic, repetitive, and participatory. The involvement of traditional and religious authorities and the active participation of the community confirm that ritual communication plays an important role in the inheritance of values, the strengthening of cultural identity, and the sustainability of the traditions of the Trusmi community.